Prevalence and Relative Risk of Other Autoimmune Diseases in Subjects with Autoimmune Thyroid Disease - Boelaert, Kristien; Newby, Paul R.; Simmonds, Matthew J.; Holder, Roger L.; Carr-Smith, Jacqueline D.; Heward, Joanne M.; Manji, Nilusha; Allahabadia, Amit; Armitage, Mary; Chatterjee, Krishna V.; Lazarus, John H.; Pearce, Simon H.; et al. (The American journal of medicine, 2010)
Common autoimmune disorders tend to coexist in the same subjects and to cluster in families. We performed a cross-sectional multicenter study of 3286 Caucasian subjects (2791 with Graves' disease; 495 with Hashimoto's thyroiditis) attending UK hospital thyroid clinics to quantify the prevalence of coexisting autoimmune disorders. All subjects completed a structured questionnaire seeking a personal and parental history of common autoimmune disorders, as well as a history of hyperthyroidism or hypothyroidism among parents. The frequency of another autoimmune disorder was 9.67% in Graves' disease and 14.3% in Hashimoto's thyroiditis index cases ( P = . 005). Rheumatoid arthritis was the most common coexisting autoimmune disorder (found in 3.15% of Graves' disease and 4.24% of Hashimoto's thyroiditis cases). Relative risks of almost all other autoimmune diseases in Graves' disease or Hashimoto's thyroiditis were significantly increased (>10 for pernicious anemia, systemic lupus erythematosus, Addison's disease, celiac disease, and vitiligo). There was relative “clustering” of Graves' disease in the index case with parental hyperthyroidism and of Hashimoto's thyroiditis in the index case with parental hypothyroidism. Relative risks for most other coexisting autoimmune disorders were markedly increased among parents of index cases. This is one of the largest studies to date to quantify the risk of diagnosis of coexisting autoimmune diseases in more than 3000 index cases with well-characterized Graves' disease or Hashimoto's thyroiditis. These risks highlight the importance of screening for other autoimmune diagnoses if subjects with autoimmune thyroid disease present with new or nonspecific symptoms.